FAKTOR PENYEBAB KESULITAN BELAJAR PESERTA DIDIK DI KELAS X SMA N 13 PADANG - Mardila, Yola - (Bimbingan dan Konseling, 2014)
The background of this research was the students showed the bad attitude in learning process,got the low mark, do not learn about the material that gave by teacher before, the students do not pastin do the exercise, the students is often disturb their friend in learning process, and showed the badbehavior such as to play truant, go home early. The purpose of this research describes: 1) The internalfactors cause difficulty in learning process by students. 2) The external factors cause difficulty inlearning process by students. This research is descriptive quantitative. Population is students of classX that have difficulty in learning process which do not get the target in Kriteria Ketuntasan Minimal(KKM), amounting 119 students. Sample is using total sampling, population is as sample. The total ofthe sample in this research is 119 students. The sources of the data is Primer data and Sekunder data.Instruments that used by researcher was questionnaire. Technique to analysis was Mean Hipotetic.The result of this research found that: 1) The internal factors cause difficulty in learning process bystudents in high category. 2) The external factors cause difficulty in learning process by students incategory high enough. Based on this result of research, it found that factors internal and external werefactors that make students were difficulty in learning process. Researcher suggest to students and allcommunity in the school to comprehend about the factor of difficulty in learning process thatstudentsâ have